Assay of Tylosin in Pharmaceutical Formulations by Visible Spectrophotometry - V.S.S Prasad, Adapa; S.P. Sastry, Chilukuri (Asian Journal of Chemistry, 2010)
Simple spectrophotometric methods (M1 and M2) for the assay of tylosin (TS) in pharmaceuticals are described. Method M1 is based on the formation of oxidative coupling product of tylosin with 3-methyl-2-benzothiazolinone hydrazone (MBTH) in the presence of ferric chloride (Fe(III) λmax 640 nm). Method M2 is based on the formation of a coloured charge transfer complex between TS and chloranilic acid (CA) (λmax 520 nm). Beer's law limits, precision and accuracy of the methods are checked by the UV reference method. The methods are found to be suitable for the assay of tylosin in pharmaceutical formulations. The per cent recoveries range from 99.02 to 100.96.